2021
DOI: 10.1002/cyto.b.21995
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry detection of CD138 expression continuum between monotypic B and plasma cells is associated with both high IgM peak levels and MYD88 mutation and contributes to diagnosis of Waldenström macroglobulinemia

Abstract: Background: Differential diagnosis of Waldenström macroglobulinemia (WM) with other indolent B-cell malignancies is still a challenge. Here, we propose an original and simple analysis of routine flow cytometry (FCM) unraveling the characteristic ongoing plasma cell (PC) differentiation of WM tumor B-cells.Methods: FCM analysis of both B-cells and PC was performed on a series of 77 patients with IgM peak. MYD88 and CXCR4 mutations were studied using an allele-specific PCR and by high throughput sequencing.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The most striking aspect is the intratumor cell fate heterogeneity, ranging from mature B cells to PCs, suggesting an ongoing PC differentiation from clonal B cells believed to be memory like cells with PC differentiation ability [123]. In line with this, recent flow cytometry analysis revealed a continuum of the PC marker CD138 expression between the malignant B‐cell subset and the more differentiated subset infiltrating the BM [124]. Part of these differentiated WM tumor cells, the plasmacytoid lymphocytes, co‐expressed the pan‐B‐cell markers CD19 and CD20.…”
Section: Distinct Layers Of Plasma Cell Heterogeneitymentioning
confidence: 99%
“…The most striking aspect is the intratumor cell fate heterogeneity, ranging from mature B cells to PCs, suggesting an ongoing PC differentiation from clonal B cells believed to be memory like cells with PC differentiation ability [123]. In line with this, recent flow cytometry analysis revealed a continuum of the PC marker CD138 expression between the malignant B‐cell subset and the more differentiated subset infiltrating the BM [124]. Part of these differentiated WM tumor cells, the plasmacytoid lymphocytes, co‐expressed the pan‐B‐cell markers CD19 and CD20.…”
Section: Distinct Layers Of Plasma Cell Heterogeneitymentioning
confidence: 99%
“…have recently highlighted the role of CXCR4 in WM and its possible use as a therapeutic target ( 377 ). Additionally, CD138 has recently emerged as a potentially identifying feature of WM tumor cells, associated with IgM peaks and MYD88 mutations ( 378 ). Recent research has shown the role of nanoscale organization of CARs and TCRs for CAR-T cells targeting CD138 with yet unknown consequences ( 379 ).…”
Section: Waldenström’s Macroglobulinemiamentioning
confidence: 99%
“…Being specific of WM, clonal cells exhibit a continuous differentiation between the small mature lymphocyte and the mature plasma cell (PC). We recently demonstrated that this unique characteristic may be used as a biological marker for WM diagnosis by evidencing the B-cell clonality in both lymphocytes and plasma cell by flow cytometry [1]. Similar to other lymphomas, cytogenetic and molecular abnormalities have been identified and can be used as prognostic factors.…”
Section: Introductionmentioning
confidence: 99%